PENGARUH KOMUNIKASI INTERPERSONAL ANTARA CREDIT MARKETING OFFICER DAN DEALER TERHADAP PENINGKATAN VOLUME PENJUALAN KENDERAAN RODA DUA DI PT.MEGA CENTRE FINANCE MEDAN - Wahidin Pardosi; Aswan Jaya (Lembaga Penenlitian dan Pengabdian kepada Masyarakat Universitas Darma Agung, 2020)
This study aims at finding out whether Interpersonal Communication between Credit Marketing Officers and Dealers has an effect on the increase in Sales Volume of Two Wheeler Vehicles at PT. Mega Central Finance Medan. The researchers used a quantitative descriptive approach in looking for a variable relationship. The phenomenon that occurs at PT. Mega Central Finance is the low interpersonal communication that creates credit marketing officers to dealers as service entrepreneurs, many problems that arise are the administrative settlement process that involves credit by credit marketing officers when consumers apply for credit, for customers who can transfer data still have problems such as the lack of completeness of the file done by the credit marketing officer so as to suspend the disbursement of a long time, this is always in conflict with the dealer, which dealer is providing the specified time, but not done well, as well as the dealer, the dealer also overcomes the shortage in the officer credit marketing, given the high business competition in Medan City, deeper Interpersonal Communication is needed for dealers to be able to create higher sales volumes between PT. Mega Center Finance and Dealers.